The Danish welfare state: Does it have a universal future? - Green-Pedersen, Christoffer; Jensen, Carsten (Politica, 2025)
This article explores whether the Danish welfare state retains its universal character amid shifting political, economic, and demographic conditions. Drawing on comparative welfare state research, the authors examine how universality – defined by equal rights, comprehensive coverage, and adequate benefits – has evolved across different welfare domains. The study highlights how political support for universalism hinges on the perceived adequacy and fairness of welfare benefits, particularly among the middle class. While health and education services remain largely universal, areas like unemployment insurance, pensions, and housing have seen growing stratification and private alternatives. Despite significant reform activity over recent decades, the core of the universal welfare state endures, though increasingly “weathered.” The article concludes that while universality faces challenges, its survival depends on continued political commitment and public trust in the system’s fairness and effectiveness. The contributions in this special issue further illuminate the varying trajectories of universalism in key policy areas.